COMMUNICATIVE METHOD X GRAMMAR TRANSLATION METHOD: IMPACT ON MULTIPLE-CHOICE TEST SCORES - de Sousa, Bruno Jonatan; Felipe, William; Bezerra de Araújo, Rosanne (Revista UNI-RN, 2019)
ABSTRACT Facing the importance of English Leaning and the low proficiency rates in Brazil, besides the importance of this language to high education admittance, this research aimed to understand the score difference in multiple-choice tests after students participated in lessons that approached reading and writing (Group G) in comparison to those (Group C) who were part of a lesson that balanced the 4 skills — reading, writing, listening, and speaking. Although most of the students considered highly necessary to learn English, most of them were not highly motivated to learning this language at school. The scores in the Verb Agreement Section of the test were higher in the Group G (1.56). On the other hand, in the Critical Thinking Section, the Group C (2.74) had better scores. The final scores were slightly higher (5%) for the Group G, which obtained a score of 4.17, while the Group C obtained 3.96. It is important to highlight that the score difference in this study should not be taken as significant when considering that in one of the groups the students were exposed to all 4 skills, which benefits the students more consistently. RESUMO MÉTODO COMUNICATIVO X MÉTODO DE GRAMÁTICA E TRADUÇÃO: IMPACTO EM ESCORES DE TESTES DE MÚLTIPLA ESCOLHA Diante da importância da aprendizagem da Língua Inglesa e os baixos níveis de proficiência no Brasil, além da importância dessa língua para a admissão no ensino superior, este estudo objetivou entender a diferença nos escores em testes de múltipla escolha após alunos participarem de aulas que abordaram as habilidades de leitura e escrita (Grupo G) em comparação àqueles (Grupo C) que fizeram parte de uma aula que balanceou as quatro habilidades — leitura, escrita, escuta, e fala. Apesar de a maioria dos estudantes considerarem aprender inglês altamente necessário, a maioria deles não estavam altamente motivados a aprender esta língua na escola. Os escores na Sessão de Concordância Verbal do teste foram mais altos no Grupo G (1.56). Por outro lado, na Sessão de Interpretação Textual, o Grupo C (2.74) obteve melhores escores. Os escores finais were levemente maiores (5%) para o Grupo G, que obteve um escore de 4.17, enquanto o Grupo C obteve 3.96. É importante ressaltar que a diferença nos escores encontrada neste estudo não deve ser entendida como significativa ao considerar-se que um dos grupos de estudantes foram expostos às 4 habilidades, o que os beneficia de forma mais sólida.